Phylogeographic Study of Betutu Fish (Oxyeleotris marmorata) Interpreted Using DNA Barcodes in Three Rivers in East Java Region, Indonesia - Dio Aulia Widiansyah; Mohammad Fadjar; Umi Zakiyah (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Betutu (Oxyeleotris marmorata) is a freshwater fish of high economic value widely consumed in Southeast Asia. Overfishing in nature has resulted in a decline in population and genetic diversity. Genetic diversity is an important factor in the long-term survival of O. marmorata populations. This study aimed to analyze the genetic diversity and phylogenetic relationships of O. marmorata in three rivers in East Java (Bengawan Solo River, Kali Tengah River, and Bondoyudo River) using a DNA barcoding approach. Twenty-two fish specimens were collected, identified, and analyzed using PCR and DNA sequencing. The results showed that O. marmorata from the three locations had a low level of genetic variation, with genetic distance differences between 0.00-0.02. Phylogenetic analysis showed that specimens from East Java were closely related to populations from Thailand and Australia. This study emphasizes the importance of genetic conservation and population management with the development of hatcheries to reduce dependence on natural catch.